Peran Tenaga Kerja Wanita (TKW) dalam Menopang Ekonomi Keluarga di Kecamatan Aimere Kabupaten Ngada - Naja, Lidia; Sagajoka, Estherlina; Penu, Yustina Paulina (JURNAL EQUILIBRIUM, 2022)
This study aims to determine the role of former female workers (TKW) in supporting the family economy. The method used is Descriptive Qualitative. The data sources in this study used primary data and secondary data. The results of this study show that the role of former female workers (TKW) in supporting the family economy in Aimere District has reached the criteria of being very successful. Because: 1) Female Labor plays a role in the public domain and has shown that former female workers (TKW) engage in activities outside the home that bring income. Activities outside the home by former female workers are managing a 24% sewing business, 40% stall business, 19% food stall business, 17% bakery business and 1% internet café business. This effort has achieved success in helping to meet the needs of families who are deemed inadequate. 2) domestic roles performed by former female workers in addition to working in the public sphere they also play an active role in the family, namely: taking care of children, taking care of husbands, cooking, washing and cleaning the house. Therefore, the role of former female workers (TKW) in sustaining the family economy has been recognized by the husband that his wife plays a very important role in a household. The involvement of the wife working as a TKW abroad carries positive implications for her family's economy.